(untitled) (Third Sector Social Economic Review, 2022)
The aim of this study was to determine the effect of organizational spirituality perceptions of individuals in managerial positions on their life satisfaction levels. In addition, it was aimed to determine whether the participants’ organizational spirituality and life satisfaction levels differ according to their demographic characteristics. The data were collected from 101 managers working at different levels of management in Kahramanmaraş textile companies. In the study, the “Organizational Spirituality Scale” consisting of 21 items, and the “Life Satisfaction Scale” consisting of 5 items, were used. The data were analyzed using the SPSS 24.0 statistical program. According to the results of the research, the perception of organizational spirituality in managers positively affects their level of life satisfaction. In addition, while managers’ perceptions of organizational spirituality differed only according to age variable, it was determined that life satisfaction levels differ according to age and income variables.